Comparison of Handgrip Strength among Diabetes Mellitus with and without Cervical Radiculopathy - Fayza Mushtaq, Mirza M Farooq, Khusboo Gulzar, Farooq Islam, Shahrayar Asgher, Fatima Kalsoom, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients with Diabetes Mellitus type 2 have reported to be more disabled in self-care tasks and other daily living activities because of many hand complications. There is reduction in grip strength in diabetic population. The purpose of this study was to compare hand grip strength among diabetes mellitus with and without cervical radiculopathy. A dynamometer can be used to swiftly and precisely measure the link between diabetic patient’s hand grip strength and their blood sugar levels. Objective(s): The study's objective was to evaluate the comparison of hand grip strength among diabetes mellitus with and without cervical radiculopathy. Methodology: A Cross-sectional study was carried among 385 diabetic patients with and without cervical radiculopathy from age 35-75. Data collected from two hospitals of Gujrat City. The study was completed June 2022 to October 2022 within 4 months by non-probability convenient sampling. Both genders were included. Instruments used in this study were handheld dynamometer. We were start to measure handgrip strength in both dominant and non-dominant hand of diabetic patients with and without cervical radiculopathy. Result was analyzed by SPSS version 24; mean and standard deviation were calculated for quantitative variables whereas frequency and percentages were used for qualitative variables. Results: The results had been obtained from 385 diabetic patients (50.6%) were females and (49.4%) were males. In our study the data was collected on the bases of age, gender, socioeconomic status, area and dominancy of hand. 61(32.28%) diabetic patients with cervical radiculopathy hand grip strength are more effected as compared to those without cervical radiculopathy that were 15(7.94%) and there (P<0.001) which indicates it is statistically significant. Practical Implication: The study suggests that fewer patients were diagnosed with cervical radiculopathy in diabetic patients and more patients were without cervical radiculopathy. Conclusion(s): This study concluded that the hand grip strength of patients with cervical radiculopathy prone to diabetes was affected highly as compared to those of which were not diagnosed with cervical radiculopathy but with diabetes. Although our study suggests that less patients were diagnosed with cervical radiculopathy in diabetic patients and more patients were without cervical radiculopathy, our study also proves that diabetic patients are also likely to develop neuropathies in later ages. Keywords: Hand grip strength, Handheld Dynamometer, Cervical Radiculopathy, Diabetes Mellitus